Effect of CpG dinucleotides within IgH switch region repeats on immunoglobulin class switch recombination. Issue 2 (August 2015) - Zhang, Zheng Z.; Hsieh, Chih-Lin; Okitsu, Cindy Yen; Han, Li; Yu, Kefei; Lieber, Michael R.
Highlights The CpG motif is rare within mammalian IgH class switch recombination repeats. Two CpG sites per 80 bp synthetic Sα switch repeat induces methylation at the Iα, resulting in lower transcription. CpG sites within the repetitive Sα region trigger DNA methylation around the promoter. Ig switch repeats evolved to have few CpG sites to avoid suppression of the promoter.